-3(1-9z)-(-11z-11)=

Simple and best practice solution for -3(1-9z)-(-11z-11)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(1-9z)-(-11z-11)= equation:


Simplifying
-3(1 + -9z) + -1(-11z + -11) = 0
(1 * -3 + -9z * -3) + -1(-11z + -11) = 0
(-3 + 27z) + -1(-11z + -11) = 0

Reorder the terms:
-3 + 27z + -1(-11 + -11z) = 0
-3 + 27z + (-11 * -1 + -11z * -1) = 0
-3 + 27z + (11 + 11z) = 0

Reorder the terms:
-3 + 11 + 27z + 11z = 0

Combine like terms: -3 + 11 = 8
8 + 27z + 11z = 0

Combine like terms: 27z + 11z = 38z
8 + 38z = 0

Solving
8 + 38z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 38z = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 38z = 0 + -8
38z = 0 + -8

Combine like terms: 0 + -8 = -8
38z = -8

Divide each side by '38'.
z = -0.2105263158

Simplifying
z = -0.2105263158

See similar equations:

| 3(-7-2x)+6(3x-7)=-51 | | 2x-6x+3x= | | 34=-2(2p+5)+5(1-7p) | | X=1.75+1.75X | | 3(t+7)-4=17 | | -4n-4(n-1)=12 | | 5=1+n-2 | | 5x^3+14x^2-3x=0 | | -(1-6x)-5=12 | | (a^4*-ac)+(c^3*d^2)= | | 5/7x15 | | 15x+25y=1400 | | c/5-c-1/10=9/10 | | 5X+7-2x=-11 | | 2y-10x=70 | | 17=3t+5 | | 5x-3y+2x+y= | | 6=3s-3 | | 3.12-d+2.1=1.910 | | (8+7i)-(-2+3i)= | | c-2.2+7.35=9.2 | | 2x+81=99 | | B-4.14=2.13-1.14 | | (X^2)-(0.5x)-(0.6)=0 | | -6+n=-2n | | C-2.2+7.35=9.3 | | x3=27/64 | | Log[5](2-4x)=1 | | 1+8v=7v | | -9z=-10z+3 | | 3y+-4=11 | | -6+4m=5m |

Equations solver categories